Karawitan Music Art in Shaping the Self-Esteem of Blind Sensory Disability - Astuti, Revy Anindyta Dwi; Khairi, Alfin Miftahul (Department of Special Education, 2024)
Abstract: Musical art is a bridge for visually impaired people to show themselves and appreciate their own abilities. This research aims to describe the formation of self-esteem in people with visual and sensory disabilities through the art of musical music. The method used is qualitative, using a phenomenological approach. The results of this study indicate that the values contained in karawitan, namely the values of togetherness (cooperation), leadership, responsibility, leadership, love of culture, discipline, and religion, have an impact on four aspects of self-esteem: power, significance, benevolence, and expertise. The self-esteem possessed by beneficiaries through the art of karawitan music is known to be positive, as shown by the karawitan values they have that can form all four aspects.